Development of hardware for digital control system of pulsed NQR spectrometer - Safronov, Igor; Kazemirskiy, Taras; Samila, Andrii (IEEE, 2021)
The analysis is carried out and the choice of the optimal type of PLD for the implementation of a digital control system for a pulsed coherent NQR spectrometer is proposed. Structural and functional synthesis of electronic devices based on FPGA EP1C6T144C8N has been carried out. The development can also be used in the study of the operation of programmable logic integrated circuits for deepening knowledge and skills in the languages for describing equipment for modeling electronic systems – Verilog HDL, VHDL.
Keywords: programmable logic devices; FPGA; hardware; radiospectrometer; NQR